2022
DOI: 10.1017/s0016756822000462
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in the Niagara Escarpment in Ontario, Canada: distribution, connectivity, and geohazard implications

Abstract: The Niagara Escarpment is a geological feature located in southern Ontario, Canada, and the northeastern United States, comprising highly fractured sandstone, shale and carbonates deposited during the Ordovician and Silurian periods. Differential erosion of the strata has generated a steep cliff face which bisects the city of Hamilton, Ontario. Geological fractures are widespread in the escarpment and result in the formation of unstable blocks of rock subject to erosion through rockfall. This presents structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…However, the details of their interactions, for example relative ages, termination styles and cross cutting relationships and interactions cannot be confidently ascertained using these data. Nonetheless, on the photogrammetry results (Figs 11 and 12), the fractures are more readily observable at site B compared to site D. The FracPaQ fracture quantification results on the other hand do allow us to make such interpretations, albeit in 2D, which is somewhat problematic given the 3D nature of fracture networks (Formenti et al 2022), but not an issue unique to this case study on microdrone utility. On the FracPaQ results, some along-coast variation in the orientation of the two interpreted perpendicular fracture sets is apparent.…”
Section: Summary and Fracture Interpretationmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the details of their interactions, for example relative ages, termination styles and cross cutting relationships and interactions cannot be confidently ascertained using these data. Nonetheless, on the photogrammetry results (Figs 11 and 12), the fractures are more readily observable at site B compared to site D. The FracPaQ fracture quantification results on the other hand do allow us to make such interpretations, albeit in 2D, which is somewhat problematic given the 3D nature of fracture networks (Formenti et al 2022), but not an issue unique to this case study on microdrone utility. On the FracPaQ results, some along-coast variation in the orientation of the two interpreted perpendicular fracture sets is apparent.…”
Section: Summary and Fracture Interpretationmentioning
confidence: 85%
“…Many studies have shown that fractures in natural rocks are rarely completely uniform or random (Watkins et al 2018, Formenti et al 2022. Instead, fracture orientations, sizes, and spatial distributions are often somewhat ordered (Healy et al 2017).…”
Section: Fracture Quantification and Mapping Methodologymentioning
confidence: 99%
“…The Niagara Escarpment traverses the city of Hamilton, a densely populated region of southern Ontario, with urban infrastructure abutting the escarpment edge and numerous roads traversing the rock face. Weathering of outcrops in this urban region has caused numerous rockfalls, resulting in major road closures and infrastructure damage (Mellies et al 2016;Formenti et al 2022). The dolostones of the escarpment face are highly fractured and interbedded with shale units, producing steep overhangs due to differential erosion and undercutting (Hewitt, 1971).…”
Section: Study Sitementioning
confidence: 99%
“…The Niagara Escarpment lies within temperate climatic region of southern Ontario, Canada and exposes Palaeozoic sedimentary strata. These rocks are subject to weathering processes and experience frequent failure events (Mellies et al 2016;Formenti et al 2022). Despite the infrastructural and safety hazards posed by the instability of the escarpment face, little is known about the actual mechanisms responsible for weathering of the escarpment and their resultant implications for fracture formation and rock failure.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological risk assessment (ERA) is a methodology for assessing and predicting the extent of ecosystem loss and degradation caused by human activities or natural hazards, in order to determine the state of ecosystem quality and the level of risk [1][2][3]. ERA provides an integrated assessment of human activities and environmental systems by identifying and linking the possible impacts of risks over long time periods and large regional scales in environmental management [4][5][6]. Ultimately, ecological environmental risk management and environmental monitoring provide decision support.…”
Section: Introductionmentioning
confidence: 99%